Extracellular Matrix Developments and Therapeutics - Sashank Madhurapantula, Rama; Orgel, Joseph P.R.O; Loewy, Zvi (Biochemistry, 2021)
Understanding extracellular matrix (ECM) structure and function is important for developing biomedical applications that are as close to 'native' as possible. Written by pioneering scientists from all over the world, this book reports research and new developments in the field of collagen structure, function, and biomechanics and discusses the relevance of hyaluronic acid and its therapeutic uses. It gives readers a glimpse of what is current in this area and we hope it piques their interest in learning more about ECM biology.